Correction: 827Spatio-Temporal Quantification of FRET in Living Cells by Fast Time-Domain FLIM: A Comparative Study of Non-Fitting Methods. - Leray, A; Padilla-Parra, S; Roul, J; Héliot, L; Tramier, M (2013)
[This corrects the article on p. e69335 in vol. 8.].